Pengaruh Pengetahuan Pelajar tentang Perbankan Syariah terhadap Minat Memilih Produk BSI: Studi Kasus Siswa Madrasah Aliyah Negeri 1 Medan - Khairussyifa, Salwa; Roka, M.H, Dr. Mustapa Khamal; Irham, M.E.I, Mawaddah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the influence of students' knowledge about Islamic Banking significantly on the interest in choosing BSI products. This research uses quantitative research methods. The population in this study was students of class XII Madrasah Aliyah Negeri 1 Medan and the sample taken was 85 respondents. Sampling is carried out by probability sampling using simple random sampling. The data collection technique uses a questionnaire measured using a likert scale. The data analysis used is multiple linear regression analysis with the help of the SPSS program. The results of the study partially with the t-test showed that the variables of agencies, products and locations did not have a positive and significant effect on the interest in choosing BSI products with a value of 0.00 < 0.05 and a fhitung > ftabel (18,317 > 2.48). The Rsquare value of 47.8% was determined by independent variables, while the remaining 52.2% was influenced by other factors outside of this study. Keywords : interest, islamic bank, knowledge.